Arbuscular Mycorrhiza-Mediated Regulation of Polyamines and Aquaporins During Abiotic Stress: Deep Insights on the Recondite Players - Sharma, Karuna; Gupta, Samta; Thokchom, Sarda Devi; Jangir, Pooja; Kapoor, Rupam (Frontiers in Plant Science, 2021)
Environmental stresses of a/biotic origin induce the production of multitudinous compounds (metabolites and proteins) as protective defense mechanisms in plants. On account of regulation of some of these very compounds, Arbuscular Mycorrhizal Fungi (AMF) reinforce plants’ inherent tolerance towards stress of different origins and kind. The paper reviews two specific fundamental mechanisms that are categorically associated with mycorrhiza in alleviating major abiotic stresses − salt, drought, and heavy metal (HM) toxicity. It constructs emphasis on Aquaporins (AQPs), the conduits of water and stress signals; and Polyamines (PAs), the primordial stress molecules, which are regulated by AMF to assure water, nutrient, ion, and redox homeostasis. Under stressful conditions, AMF-mediated host AQP responses register distinct patterns: upregulation to encourage water and nutrient uptake; downregulation to restrict water loss and HM uptake; or no alterations. The patterns thereof are apparently an integrative outcome of the duration, intensity and type of stress, AMF species, interaction of fungal AQPs with that of plants, and the host type. However, the cellular and molecular bases of mycorrhizal influence on host AQPs are largely unexplored. The roles of PAs in augmenting antioxidant defense system and improving tolerance against oxidative stress are well-evident. Exogenous employment of PAs, complemented with AMF inoculation, has been suggested as a promising approach in magnifying stress tolerance. However, the precise mechanism by which mycorrhiza accords stress tolerance by influencing the PA metabolism per se is abstruse and broadly variable under different stresses and plant species. The review comprehensively analyzes the current state-of-art of involvement of AMF in ‘PA and AQP modulation’ under abiotic stress and identifies the lesser explored landscapes, gaps in understanding and the accompanying challenges. Finally, the review outlines the prospects of AMF in realizing sustainable agriculture and provides insights into potential thrust areas of research on AMF and abiotic stress.